2020
DOI: 10.1177/2050312120936907
|View full text |Cite
|
Sign up to set email alerts
|

A narrative systematic review of tobacco cessation interventions in Sub-Saharan Africa

Abstract: Aim: In the face of increasing tobacco consumption in Sub-Saharan Africa, it is crucial to not only curb the uptake of tobacco, but to ensure that tobacco users quit. Considering the minimal attention that tobacco cessation interventions receive in Sub-Saharan Africa, this review aims to describe studies that evaluated tobacco cessation interventions in the region. Methods: A search of studies published ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…Peer et al and Mamudu et al have both pointed out that smoking cessation campaigns and tobacco control interventions are scant in SSA. 47,48 The region has been described as a "research desert" concerning tobacco control, with a clear need for increased investment in both research and training over the past 50 years. 48 The lack of comprehensive tobacco cessation interventions highlights an urgent need for SSA to prioritize and invest in effective tobacco control strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Peer et al and Mamudu et al have both pointed out that smoking cessation campaigns and tobacco control interventions are scant in SSA. 47,48 The region has been described as a "research desert" concerning tobacco control, with a clear need for increased investment in both research and training over the past 50 years. 48 The lack of comprehensive tobacco cessation interventions highlights an urgent need for SSA to prioritize and invest in effective tobacco control strategies.…”
Section: Discussionmentioning
confidence: 99%
“…They identified eight central themes as critical to providing data to support tobacco control action: patterns of tobacco use, effects of use (including impacts on sustainable development goals), populations at risk, policy and implementation, sociocultural context of tobacco use, the tobacco industry, tobacco production and alternative livelihoods and the economics of tobacco and tobacco control 33. Other researchers have identified similar research needs to support tobacco control in Africa, such as research on targeted tobacco cessation interventions25 and the household economic impacts of tobacco use 31. The fact that our review found gaps in the literature in some of these focus areas has relevance for public health practice, because such data can play an important role in developing, gaining support for and implementing tobacco control policies and programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews have examined the prevalence of smoking21 22 and policy, media and economic landscape of sub-Saharan Africa,5 the implementation of school-based prevention programmes,23 24 cessation interventions,25 the application of research study designs and methods26 and tobacco policy assessment tools 27. These studies have shown that tobacco use behaviours vary greatly across sub-Saharan African countries along with the implementation of tobacco control policies 21 28.…”
Section: Introductionmentioning
confidence: 99%
“…As suggested in the review performed in sub-Saharan Africa, better approaches for developing countries would be to identify tobacco users in the already running national programs for TB, HIV, and maternal and child health programs and incorporate the component of tobacco cessation counseling in it. [ 52 ] There is a need to individualize counselling according to the requirement of each person. [ 53 ]…”
Section: Discussionmentioning
confidence: 99%